Advances in cancer research. - Broome, Ann-Marie (Academic Press, 2018)
Advances in Cancer Research, Volume 139, provides invaluable information on the exciting and fast-moving field of cancer research. Original reviews are presented on a variety of topics relating to the rapidly developing intersection between nanotechnology and cancer research, with unique sections in the new release focusing on Exosomes as a theranostic for lung cancer, Nanotechnology and cancer immunotherapy, Ultrasound imaging agents and delivery systems, Dendronized systems for the delivery of chemotherapeutics, Thermosensitive liposomes for image-guided drug delivery, Supramolecular Chemistry in Tumor Analysis and Drug Delivery, Gold nanoparticles for delivery of cancer therapeutics, and Single cell barcode microchip for cancer research and therapy.